The Role of Customary Law in Maintaining Social Harmony in Indonesian Village Communities (Journal of Social And Education Research, 2024)
. Customary law serves as an essential social instrument in the lives of rural communities in Indonesia, functioning not only as a set of traditional norms but also as a mechanism for conflict resolution, cultural preservation, and the strengthening of social harmony. This study aims to analyze the role of customary law in maintaining social harmony within village communities through a literature review approach. Data were collected from scientific journals, books, research reports, and official publications from customary and governmental institutions published between 2007 and 2025. The analysis was conducted descriptively and qualitatively by synthesizing findings based on key themes such as the values of customary law, mechanisms of conflict resolution, harmonization between customary and national law, and its impact on social harmony. The findings indicate that customary law effectively resolves conflicts through deliberation, reconciliation, and customary sanctions, while also preserving cultural identity and reinforcing community cohesion. However, modernization and the integration of national law present challenges to its implementation. Harmonization between customary and formal legal systems is therefore crucial to maintaining the relevance of customary law while supporting social and cultural development. This study affirms that customary law remains a vital pillar in fostering harmonious, just, and culturally rooted village communities.